Kingdom of Lesotho : Joint Staff Advisory Note on the National Strategic Development Plan. (IMF Staff Country Reports; Country Report ;, 2012)
Lesotho's National Strategic Development Plan (NSDP) serves as an implementation strategy for the national vision. It recognizes the significant challenges Lesotho faces in reducing poverty and making growth more broad-based. Overall, it presents a coherent analysis and offers an appropriate path forward to sustained poverty reduction and sustainable economic growth. Executive Directors find that a well-designed implementation and monitoring framework is necessary. Implementation of the NSDP will be a key challenge.